The Neuromuscular Profile of Knee Extensor and Flexor Muscles in Professional Soccer Players in The Saudi Premier League - Alhowimel, Ahmed; Alodaibi, Faris; Khayat, Yaaqoub; Alsobayel, Hana; AlKassabi, Othman (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Purpose: The neuromuscular system of soccer players is a key factor in their competitive performance, as it determines a player’s immediate force response, reactivity and running speed during matches. The neuromuscular system has recently begun to be analyzed by tensiomyography (TMG). This study’s primary aim was to generate normative data of the mechanical and neuromuscular profile for the knee extensor and flexor muscles. Method: This study used a cross-sectional study of 83 professional soccer players from three Saudi Premier League teams at the start of the preseason period. TMG was used to measure the radial muscle belly displacement in the knee extensor and flexor muscles in both legs. Results: The results suggest that the highest degree of symmetry corresponded to the vastus medialis (83.7 ± 14.3%) and the lowest to the biceps femoris (76.1 ± 10.9%). No statistical difference was found between the dominant and non-dominant muscles, or between on-field player positions across all four tested muscles. Conclusion: The study presented normative data of a convenience sample of Saudi professional soccer players and observed that the highest asymmetry was seen in the vastus medialis and the lowest asymmetry in the biceps femoris.